Cytoplasmic Polyadenylation in Development and Beyond - Richter, Joel D. (American Society for Microbiology, 1999)
Maternal mRNA translation is regulated in large part by cytoplasmic polyadenylation. This process, which occurs in both vertebrates and invertebrates, is essential for meiosis and body patterning. In spite of the evolutionary conservation of cytoplasmic polyadenylation, many of the cis elements and trans-acting factors appear to have some species specificity. With the recent isolation and cloning of factors involved in both poly(A) elongation and deadenylation, the underlying biochemistry of these reactions is beginning to be elucidated. In addition to early development, cytoplasmic polyadenylation is now known to occur in the adult brain, and there is circumstantial evidence that this process occurs at synapses, where it could mediate the long-lasting phase of long-term potentiation, which is probably the basis of learning and memory. Finally, there may be multiple mechanisms by which polyadenylation promotes translation. Important questions yet to be answered in the field of cytoplasmic polyadenylation are addressed.